المقروئية لترجمة آيات الأمر القرآنية الواردة في القرآن الكريم ترجمة تفسيرية - Al Farisi, Mohamad Zaka (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2021)
The stylistics of the Quran often becomes obstacles in translation. In the Quran, many imperative speech acts do not convey the meaning of commands yet present particular pragmatic meanings such as praying, threatening, insulting, etc. These pragmatic meanings make the translation process difficult. The difficulty occurs because the translator faces speech acts with a different sentence meaning from its utterance meaning. This research aims to reveal the readability of the translation of the imperative verses that have particular pragmatic meanings. In this regard, the research samples were taken purposively in the form of imperative verses of the Quran with certain pragmatic meanings. The unit of analysis is the translation of these imperative verses, which are included in the Al-Qur'anul Karim Tarjamah Tafsiriyah by Muhammad Thalib. Apart from using the cloze test, the readability analysis is also based on the respondents' perception of the readability of the translation of the imperative verses. The research findings show that the translation of the imperative verses in Al-Qur'anul Karim Tarjamah Tafsiriyah has a high degree of readability. This finding is reinforced by the results of the cloze test, which shows that the translation of these imperative verses is at an independent level; namely, readers can understand the translation without the need for help from others. The high readability of the translation of these imperative verses, among other things, is due to the use of several translation techniques, such as literal, transposition, reduction, and amplification techniques that are applied in both single and couplet procedures.